Carbon nanotubes and other fullerenes produced from tire powder injected into an electric arc - Murr, L.E.; Brown, D.K.; Esquivel, E.V.; Ponda, T.D.; Martinez, F.; Virgen, A.
A novel method of growing multiwall carbon nanotubes by injecting tire powder into an electric arc has been developed. The process is optimized using a DC electric arc in pressurized helium. The multiwall carbon nanotube product and the optimization process are characterized by transmission electron microscopy. D 2005 Elsevier Inc. All rights reserved.
Keywords: MULTIWALL CARBON NANOTUBES; TIRE POWDER; ELECTRON MICROSCOPY; ELECTRIC ARC DISCHARGE